2018
DOI: 10.3164/jcbn.18-12
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of perioperative invasiveness of colorectal endoscopic submucosal dissection evaluated by energy metabolism

Abstract: The aim of this study was to assess the perioperative invasiveness of endoscopic submucosal dissection for colorectal cancer quantitatively by using energy metabolism. In fifty-three patients who underwent endoscopic submucosal dissection for colorectal cancer, resting energy expenditure using an indirect calorimeter, body weight and basal energy expenditure using the Harris–Benedict equation before and after endoscopic submucosal dissection. Resting energy expenditure/body weight and resting energy expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…According to Long’s method[ 28 ], the total energy expenditure is defined as the product of BEE, SF, and the activity factor, and it is theoretically the same as the REE measured at rest. Since the activity factor on the day of ESD is the same as that on postoperative day (POD) 1, the SF on POD 1 can be calculated by setting SF on the day to be 1.0[ 33 , 34 ]. From the above, SF is a marker indicating the degree of hypermetabolic state[ 33 , 34 ].…”
Section: Assessment Of Physical Stress By Energy Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Long’s method[ 28 ], the total energy expenditure is defined as the product of BEE, SF, and the activity factor, and it is theoretically the same as the REE measured at rest. Since the activity factor on the day of ESD is the same as that on postoperative day (POD) 1, the SF on POD 1 can be calculated by setting SF on the day to be 1.0[ 33 , 34 ]. From the above, SF is a marker indicating the degree of hypermetabolic state[ 33 , 34 ].…”
Section: Assessment Of Physical Stress By Energy Metabolismmentioning
confidence: 99%
“…Since the activity factor on the day of ESD is the same as that on postoperative day (POD) 1, the SF on POD 1 can be calculated by setting SF on the day to be 1.0[ 33 , 34 ]. From the above, SF is a marker indicating the degree of hypermetabolic state[ 33 , 34 ]. The values of SFs are recognized as 1.1 for low invasiveness, 1.2 for medium invasiveness, and 1.8 for high invasiveness[ 28 ], and these values are used as indicators to determine perioperative energy management.…”
Section: Assessment Of Physical Stress By Energy Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies, which measured the change in energy metabolism using an indirect calorimeter and Long’s method, revealed that the degree of invasion during the perioperative period of ESD was lower than that during surgery. ( 6 , 7 ) Another study also showed that salivary amylase activity was increased by the physical stress associated with gastric ESD, including pain. ( 8 ) Previously, the invasiveness of surgery had been evaluated by measuring the levels of catecholamine, cortisol, adrenocorticotropic hormone, blood sugar, blood insulin or interleukin-6.…”
Section: Introductionmentioning
confidence: 99%